Craftivism Between Nationalism and Activism in Ukraine and Belarus - Myzelev, Alla (Frontiers in Sociology, 2022)
This article outlines the history and significance of Craftivism in Eastern Europe. Using two case studies of artists it investigates the use of the craft language in Eastern Europe and its usability for activism. Do-It-Yourself culture, of which Craftivism is part, rejects the commercialism, gender norms and the conventional lifestyle in the Global North. Use of crafts as a language of political and social struggle allows to convey the message in a less confrontational but nevertheless very pertinent way. The craftivism is a successful language for the feminist political struggle in the Eastern Europe.